Identifying Components of a Halobacterium salinarum N-Glycosylation Pathway - Vershinin, Zlata; Zaretsky, Marianna; Guan, Ziqiang; Eichler, Jerry (Frontiers in Microbiology, 2021)
Whereas N-glycosylation is a seemingly universal process in Archaea, pathways of N-glycosylation have only been experimentally verified in a mere handful of species. Towards expanding the number of delineated archaeal N-glycosylation pathways, the involvement of the putative Halobacterium salinarum glycosyltransferases VNG1067G, VNG1066C and VNG1062G in the assembly of an N-linked tetrasaccharide decorating glycoproteins in this species was addressed. Following deletion of each encoding gene, the impact on N-glycosylation of the S-layer glycoprotein and archaellins, major glycoproteins in this organism, was assessed by mass spectrometry. Likewise, the pool of dolichol phosphate, the lipid upon which this glycan is assembled, was also considered in each deletion strain. Finally, the impacts of such deletions were characterized in a series of biochemical, structural and physiological assays. The results revealed that VNG1067G, VNG1066C and VNG1062G, renamed Agl25, Agl26 and Agl27 according to the nomenclature used for archaeal N-glycosylation pathway components, are responsible for adding the second, third and fourth sugars of the N-linked tetrasaccharide decorating Hbt. salinarum glycoproteins. Moreover, this study demonstrated how compromised N-glycosylation affects various facets of Hbt. salinarum cell behavior, including the transcription of archaellin-encoding genes.